Hypersatellite Kα Production in Trapped Ar Ions at KK Trielectronic Recombination Energies - Biela-Nowaczyk, Weronika (2023)
Funding Information: W.B.-N. acknowledges DSC Grant MNiSzW Nr 7150/E-338/M/2018, the GET_INvolved Programme at FAIR/GSI (www.fair-center.eu/get_involved) and the JIPhD program through contract POWR.03.05.00-00-Z309/17-00. D.S.L.M. acknowledges the Kosciuszko Foundation. P.A and F.G acknowledge the FCT through project number UID/04559/2020 (LIBPhys). Publisher Copyright: © 2023 by the authors.